Urinary pCO2 Monitoring System with a Planar Severinghaus Type Sensor. Issue 10 (12th April 2022) - Atherton, James G.; Pendley, Bradford D.; Guzinski, Marcin; Bissler, John J.; Lindner, Ernő
Abstract: A urinary pCO2 measurement system with a miniature planar CO2 probe has been developed for monitoring pCO2 levels in the urine (U‐pCO2 ) of catheterized septic shock patients. U‐pCO2 may provide timely recognition of changes in the microcirculatory status of patients and used as an "early" warning of metabolic‐cellular dysfunction. The utility of the U‐pCO2 sensor has been demonstrated in monitoring experiments in a model bladder. The agreement between U‐pCO2 values measured with the planar pCO2 probe and a commercial pCO2 probe in pooled urine samples projects the possibility of the implementation of the U‐pCO2 measurement system for bedside monitoring. Abstract :